Pengembangan Smart Tourism berbasis E-Government pada Dinas Kebudayaan dan Pariwisata Provinsi Jambi - Saro, Dewi Novita; Herdiansyah, Izman; Negara, Edi Surya; Sutabri, Tata (LPPM UNIVERSITAS BINA INSAN, 2024)
All activities, including tourism businesses, can now become more productive and efficient with the rapid development of information, communication, and technology (ICT). The government of a region plays a significant role in managing tourism. In line with Presidential Instruction No. 3 of 2003, which regulates the implementation of electronic government in Indonesia, it mandates the application of e-Government. By utilizing e-Government to be more flexible and user-friendly, the bureaucratic and rigid impression of government services can be eliminated. Additionally, e-Government provides public services that can be accessed anytime, from anywhere.